P013 Novel immunomodulatory role of food bioactive peptide lunasin in the healthy human intestinal mucosa. (25th January 2019) - Fernández-Tomé, S; Pérez-Rodríguez, L; Marin, A C; Indiano-Romacho, P; Ortega-Moreno, L; Casanova, M J; Moreno-Monteagudo, J A; Santander, C; Chaparro, M; Gisbert, J P; Hernández-Ledesma, B; Bernardo, D
Abstract: Background: The gastrointestinal mucosa represents the main interface between dietary components and the organism. Lunasin is a 43-amino acid peptide naturally present in soybean protein with a variety of biological functions demonstrated by in vitro assays, cell cultures and animal models. Nevertheless, its physiological relevance in human primary intestinal cells remains elusive. Methods: Peptide was obtained by chemical synthesis. Human colonic biopsies were obtained from healthy controls and conditioned with peptide lunasin (5, 50, and 200 µM), both in the presence and absence of pro-inflammatory lipopolysaccharide (LPS, 100 ng/ml). Peptide integrity during overnight culture was monitored by liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). After culture, the relative gene expression of colonic biopsies as well as the intestinal cytokine milieu in culture supernatants were characterised. Results: HPLC-MS/MS analysis showed that lunasin maintained its stability during biopsy culture up to 90%. Lunasin was bioactive in the human mucosa inducing IL-1β, TNF-α, IL-17A, CCL2, and PGE2/COX-2 gene expression, typically in a dose-dependent manner. Moreover, lunasin also enhanced mucosal expression of tolerogenic cytokines IL-10 and TGFβ and down-regulated the expression of iNOS and subunit p65 from NF-κB. LPS induced a pro-inflammatory immune response which was, however, partially abrogated in the presence of lunasin as it down-regulated pro-inflammatory IL-17A and IFN-γ, and enhanced mucosal gene expression of regulatory IL-10 and TGFβ. Moreover, results were further validated at the protein level as IL-1β, TNF-α, and IL-10 secretion were enhanced while IL-6, CCL2, and IFN-γ production were abrogated by lunasin. Indeed, the latter cytokine was also neutralised in the presence of LPS. Conclusions: Food-derived peptide lunasin is biologically active in the human intestinal mucosa determined by changes on the global cytokine milieu both at the messenger and protein levels. Lunasin displayed its anti-inflammatory effect by abrogating the production of pro-inflammatory cytokines even in the presence of LPS, and expanding the production of tolerogenic IL-10 and TGFβ. This peptide might represent, therefore, a novel agent as functional compound for the prevention of immune and inflammatory-mediated intestinal disorders.